1979
DOI: 10.1038/ki.1979.172
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up of peritoneal clearances in patients undergoing continuous ambulatory peritoneal dialysis

Abstract: Continuous ambulatory peritoneal dialysis (CAPD) might result in peritoneal membrane changes. First, CAPD exposes essentially continuously the peritoneum to peritoneal dialysis solutions. Such solutions differ from the usual extracellular fluid bathing peritoneal tissues. Second, this technique may be complicated by an increased frequency of peritonitis when compared to intermittent peritoneal dialysis. We undertook a prospective study of patients undergoing CAPD to determine if there were decreases in periton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

1981
1981
2004
2004

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…Neither Rubin et al [19] in a longitudinal study in 12 patients with a follow-up of maximal I year nor Nikolakakis et al [4] reported significant changes in ultrafiltra tion. However, loss of fluid removal capacity in CAPD patients has been found in several other studies with an incidence varying from 1.3 to 100% [5, 25 30-34].…”
Section: Discussionmentioning
confidence: 98%
“…Neither Rubin et al [19] in a longitudinal study in 12 patients with a follow-up of maximal I year nor Nikolakakis et al [4] reported significant changes in ultrafiltra tion. However, loss of fluid removal capacity in CAPD patients has been found in several other studies with an incidence varying from 1.3 to 100% [5, 25 30-34].…”
Section: Discussionmentioning
confidence: 98%
“…Frequent episodes of peri tonitis are associated with a loss of lean body mass as assessed by total body potassium measurements [II]. lilumenkrantz [5] suggests these protein losses may be pro longed, whereas in studies reported elsewhere, protein con centration during hourly exchanges had returned to control values I week follow ing an episode of peritonitis [12]. The studies reported here were not designed to determine when protein losses in dialysate returned to control values fol lowing an episode of peritonitis.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical peritonitis in CAPD patients is associated with decreases in ultrafiltration, increases in protein losses in dialysate, and increases in net glucose absorption [14,21], Return to normal functions is associated with recovery of normal transport characteristics [21,22]. Verger et al [14] also injured the mésothélium in rats using a drying technique and found similar decreases in ultrafiltration and increases in both protein dialysate and net glucose absorption.…”
Section: Discussionmentioning
confidence: 98%